Elevated pCO2 Induced Physiological, Molecular and Metabolic Changes in Nannochloropsis Oceanica and Its Effects on Trophic Transfer - Liang, Chengwei; Zhang, Yufei; Gu, Zipeng; Ren, Yudong; Zhang, Xiaowen; Xu, Dong; Ye, Naihao (Frontiers in Marine Science, 2022)
The rise of dissolution of anthropogenic CO2 into the ocean alters marine carbonate chemistry and then results in ocean acidification (OA). It has been observed that OA induced different effects on different microalgae. In this study, we explored the physiological and biochemical changes in Nannochloropsis oceanica in response to increased atmospheric carbon dioxide and tested the effect of ocean acidification (OA) on the food web through animal feeding experiments at a laboratory scale. We found that the levels of C, N, C/N, Fv/Fm, and photosynthetic carbon fixation rate of algae cells were increased under high carbon dioxide concentration. Under short-term acidification, soluble carbohydrate, protein, and proportion of unsaturated fatty acids in cells were significantly increased. Under long-term acidification, the proportion of polyunsaturated fatty acids (PUFAs) (~33.83%) increased compared with that in control (~30.89%), but total protein decreased significantly compared with the control. Transcriptome and metabonomics analysis showed that the differential expression of genes in some metabolic pathways was not significant in short-term acidification, but most genes in the Calvin cycle were significantly downregulated. Under long-term acidification, the Calvin cycle, fatty acid biosynthesis, TAG synthesis, and nitrogen assimilation pathways were significantly downregulated, but the fatty acid β-oxidation pathway was significantly upregulated. Metabolome results showed that under long-term acidification, the levels of some amino acids increased significantly, while carbohydrates decreased, and the proportion of PUFAs increased. The rotifer Brachionus plicatilis grew slowly when fed on N. oceanica grown under short and long-term acidification conditions, and fatty acid profile analysis indicated that eicosapentaenoic acid levels increased significantly under long-term acidification in both N. oceanica (~9.48%) and its consumer B. Plicatilis (~27.67%). It can be seen that N. oceanica formed a specific adaptation mechanism to OA by regulating carbon and nitrogen metabolism, and at the same time caused changes of cellular metabolic components. Although PUFAs were increased, they still had adverse effects on downstream consumers.